Asuhan Keperawatan Gerontik pada Ny.A dengan Penerapan Terapi Senam Kaki Diabetes dalam Menurunkan Kadar Glukosa Darah Penderita Diabetes Mellitus di Wilayah Kerja Puskesmas Sei Langkai Kota Batam - Yosi Melinda Gultom; Nelli Roza (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus is a chronic disease that occurs when the pancreas cannot produce enough insulin (a hormone that regulates blood sugar or glucose) or when the body cannot use insulin effectively. According to the International Diabetes Federation, the prevalence of diabetes mellitus is increasing every year in the world, reaching 537 million people suffering from diabetes in the world. Currently, Indonesia ranks sixth as the country with the highest number of people with diabetes mellitus. At the Sei Langkai Health Center in the last 6 months (January-June) there were 40 people. This professional scientific paper aims to provide gerontic nursing care to Mrs.A with the application of diabetic foot exercise therapy in reducing blood glucose levels in patients with diabetes mellitus in the Sei Langkai Health Center Working Area. The method used in this Professional Scientific Writing is a case study conducted based on the stages of nursing care including assessment, diagnosis, intervention, implementation and nursing evaluation. The results showed a decrease in blood glucose levels from the first day of GDS examination results of 215 mg/dl and on day four down to 158 mg/dl, as well as decreased drowsiness, fatigue / fatigue decreased in accordance with the expected goals and criteria. For patients, it is hoped that it can provide knowledge and insight, and can know and understand foot exercise therapy can reduce blood glucose levels in patients with diabetes mellitus.